Human Factors Analysis and Traffic Accident Prevention Program for Motorcycle Drivers: A Systematic Review - Dani Nasirul Haqi; Endang Dwiyanti; Yustinus Denny Ardyanto Wahyudiono; Bian Shabri Putri Irwanto (Health Dynamics, 2026)
Background: The human factor is the main factor in determining the success of traffic safety. The existence of human factors needs to be analyzed in more depth to create a more appropriate accident prevention program. This systematic review aims to investigate human factors, namely motorcycle drivers, causing traffic accidents and determine more effective accident prevention programs. Methods: The method used was a systematic review on electronic data sources such as ScienceDirect, ProQuest, PubMed, and Google Scholar using the keywords “human factor, traffic accident prevention program, and two-wheeled motorcycle driver”. Using the inclusion and exclusion criteria in the final stage, nineteen articles were found. Results: Human factors are the primary cause of traffic accidents involving motorcyclists, with two main aspects standing out most prominently. First, the high rate of traffic violations, such as speeding, running red lights, failing to maintain a safe distance, and aggressive driving behavior. Second, low compliance with the use of safety equipment, such as not wearing a standard helmet, protective jacket, gloves, or other safety gear. Ongoing specialized education and training programs are the most effective strategy. Conclusion: Human factors are the leading cause of traffic accidents, particularly among motorcyclists. The most effective preventive measure is through ongoing education and training programs.